Long-term VTE treatment with rivaroxaban: Results from the DRESDEN NOAC REGISTRY. Issue 208 (December 2021) - Marten, Sandra; Naue, Christiane; Tittl, Luise; Bornhauser, Martin; Beyer-Westendorf, Jan
Abstract: Data on long-term effectiveness and safety of venous thromboembolism (VTE) treatment with rivaroxaban are scarce and not available from randomized clinical trials. To supplement the positive results of phase III VTE treatment trials with rivaroxaban, we used data from the ongoing, prospective, non-interventional DRESDEN NOAC REGISTRY to evaluate long-term management patterns and clinical outcomes. Between December 1st 2011 and September 30th 2020, 812 patients with acute VTE (575 DVT; 237 PE) and rivaroxaban treatment were prospectively followed. During treatment (median rivaroxaban exposure 1.1 years IQR 0.3–5.0 years; median follow-up 6.1 years IQR 4.7–7.8 years) rates of recurrent VTE and ISTH major bleeding were 0.7/100 pt. years (95% CI 0.4–1.1) and 2.1/100 pt. years; 95% CI 1.5–2.8, respectively. Of the 427 patients still taking rivaroxaban at 12 months, 276 and 202 were still taking rivaroxaban at 3 and 5 years, respectively. "Scheduled end of treatment" was the leading discontinuation reason also beyond 12 months. When exposure days were divided by the number of major clinical outcomes (recurrent VTE + other major cardiovascular + ISTH major bleeding), continued rivaroxaban treatment had the longest "exposure per event" period (6398 days/event) compared to patients switching to alternative treatments (4658 days/event) or stopping anticoagulation completely (4337 days/event). Our results confirm low thrombotic and major bleeding rates for long-term VTE treatment with rivaroxaban. Beyond 12 months, scheduled treatment discontinuations still occur. Although 3–5% of patients planned for indefinite rivaroxaban therapy switched to other anticoagulants each year, the overall persistence to rivaroxaban was high. Highlights: VTE treatment with rivaroxaban was effective and safe in the EINSTEIN DVT/PE trials. Prospective DRESDEN NOAC REGISTRY complements trial results with long-term data. Over 5 years, VTE therapy with rivaroxaban resulted in low VTE recurrence and major bleeding rates. Treatment persistence was good and unfavourable outcomes were rare during rivaroxaban treatment.